Geomorphological Mapping Through Geospatial Technologies In The District of Visakhapatnam, Andhra Pradesh, India - Sridhar, B; Rao, P. Jagadeeswara; Allamraju, Aditya (International Journal of Computer Sciences and Engineering, 2018)
Geo-spatial advancements like Remote Sensing (RS) and Geographical Information Systems (GIS) play an essential job in developing thematic maps and integrating analysis for mapping, managing and monitoring the natural resources. RS and GIS technologies have advanced a new era in the field of applied geology and geomorphology. Geomorphology is the science of landforms present on the Earth’s surface and their systematic study is important and unique in order to interpret them as signatures of the past and ongoing geological processes. The present examination plans to delineate geomorphological features in the district of Visakhapatnam in view of visual image translation strategies. The study area mainly comprises Pediment slope(27.39%) followed by Structural hill(25.51%) and Pediplain shallow(18.06%).These maps would be useful in further analysis for natural Earth resources planning, management and decision making. Thematic maps of geomorphology have been generated on satellite data. Standard visual elucidation methods according to the standards given by NRSA have been followed and portrayed on-screen digitations of features.